Multiple Coordination Patterns in Infant and Adult Vocalizations. (28th September 2016) - Abney, Drew H.; Warlaumont, Anne S.; Oller, D. Kimbrough; Wallot, Sebastian; Kello, Christopher T.
Abstract : The study of vocal coordination between infants and adults has led to important insights into the development of social, cognitive, emotional, and linguistic abilities. We used an automatic system to identify vocalizations produced by infants and adults over the course of the day for fifteen infants studied longitudinally during the first 2 years of life. We measured three different types of vocal coordination: coincidence‐based, rate‐based, and cluster‐based. Coincidence‐based coordination and rate‐based coordination are established measures in the developmental literature. Cluster‐based coordination is new and measures the strength of matching in the degree to which vocalization events occur in hierarchically nested clusters. We investigated whether various coordination patterns differ as a function of vocalization type, whether different coordination patterns provide unique information about the dynamics of vocal interaction, and how the various coordination patterns each relate to infant age. All vocal coordination patterns displayed greater coordination for infant speech‐related vocalizations, adults adapted the hierarchical clustering of their vocalizations to match that of infants, and each of the three coordination patterns had unique associations with infant age. Altogether, our results indicate that vocal coordination between infants and adults is multifaceted, suggesting a complex relationship between vocal coordination and the development of vocal communication.